Anemia in Patients with Ulcerative Colitis in Remission: A Cross-Sectional Study from Pakistan - Muhammad Arsalan Qaisar, Sheraz Saleem, Aishah Ishaque, Muhammad Ubaid, Usman Javaid, Muhammad Zaman (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Anemia is an extra intestinal manifestation of inflammatory bowel disease that frequently causes complications. In inflammatory bowel disease (IBD) such as ulcerative colitis and Crohn’s disease, anemia is mostly caused by iron deficiency which impacts the patient’s quality of life [1, 2]. The present study aimed to assess the anemia in ulcerative colitis patients in remission. Methodology: A cross-sectional study was conducted on 82 ulcerative colitis patients at the Department of Medicine and Gastroenterology, Jinnah hospital, Lahore from February 2021 to January 2022. All the patients were assessed for anemia based on Mayo clinical score <3 for at least three months. Hemogram tests such as CBC, vitamin B12 serum levels, ferritin, folic acid levels, concentration of C - reactive protein (CRP), and transferrin were performed for the initial screening. Further, patients were evaluated for the determination of different causes of anemia. Patients were categorized into mild, moderate, and severe anemia cases. Oral iron, intravenous iron, and blood transfusion were given to mild, moderate, and severe anemia patients respectively. SPSS version 25 was used for data analysis. Results: Of the total 82 ulcerative colitis patients, there were 48 (58.5%) male and 34 (41.5%) females. The prevalence of anemia in ulcerative colitis patients and control was 51.2% (n=42) and 11.9% (n=5) respectively. The hemoglobin mean values in UC patients and control was 11.95 g/dL and 13.21 g/dL respectively. Out of 42 ulcerative colitis patients, the prevalence of mild, moderate, and severe anemia was 52.4% (n=22), 35.7% (n=15), and 11.9% (n=5) respectively. Iron deficiency was the prevalent etiology of anemia found in 22 (52.4%) patients followed by chronic anemia disease with iron deficiency found in 8 (21.9%). Hemoglobin level has no association with ferritin level. Hemoglobin level has no association with ferritin level. The hemoglobin level was increased with oral iron and intravenous iron by 1.6 g/dL and 2.3 g/dL respectively. Conclusion: The present study concluded that prevalence of anemia was higher in ulcerative colitis patients. The most common etiology of anemia was iron deficiency in both groups. Increased CRP and moderate activity associated to anemia disease was significantly related with comorbid anemia. Oral iron and intravenous iron could increase hemoglobin levels in ulcerative colitis associated anemia patients. Keywords: Anemia, Ulcerative Colitis, Iron deficiency